The renoprotective effect of Tibolone in sepsis-induced acute kidney injury - Bora, Ejder Saylav; Arda, Duygu Burcu; Erbas, Oytun (Biomedical papers, 2024)
Introduction. Sepsis-induced acute kidney injury (AKI) remains a major challenge in intensive care, contributing significantly to morbidity and mortality. Tibolone, known for its neuroprotective and hormonal properties, has not been explored for its potential in AKI management. This study investigates the protective effects of Tibolone and its underlying mechanisms involving Sirtuin-1 (SIRT1) and Yes-Associated Protein (YAP) in a rat sepsis model.Materials and Methods. Thirty-six female Wistar albino rats underwent cecal ligation and puncture (CLP) to induce sepsis. They were randomly assigned to control, CLP+Saline, and CLP+Tibolone groups. Tibolone was administered intraperitoneally. Biomarkers, including Sirtuin (SIRT1), Yes-associated protein (YAP), Tumor necrosis factor (TNF-α), High mobility group box 1 (HMGB1), malondialdehyde (MDA), creatinine, and urea, were assessed. Histopathological examination evaluated renal damage.Results. Tibolone administration significantly reduced plasma TNF-α, HMGB1, MDA, creatinine, and urea levels compared to the CLP+Saline group. Moreover, Tibolone elevated SIRT1 and YAP levels in kidney tissues. Histopathological examination demonstrated a significant decrease in tubular epithelial necrosis, luminal debris, dilatation, hemorrhage, and interstitial inflammation in Tibolone-treated rats.Conclusion. This study unveils the protective role of Tibolone against sepsis-induced AKI in rats. The improvements in inflammatory and oxidative biomarkers and histological evidence suggest Tibolone's potential as a therapeutic intervention in sepsis-associated kidney injury. The upregulation of SIRT1 and YAP indicates their involvement in Tibolone's renoprotective mechanisms. Further investigations are warranted to explore Tibolone's translational potential in human sepsis-induced AKI.
Keywords: Tibolone; acute renal injury; sepsis; anti-inflammatory